Urea impregnated biochar to minimize nutrients loss in paddy soils - Dimin @ Mohd Amin, Mohd Fairuz; Se, Sian Meng; Shaaban, Azizah; Hashim, Mohammad Muaz (Penerbit Universiti Malaysia Pahang, 2014)
Rubber wood sawdust (RWSD) is converted into a porous form of biochar through the slow pyrolysis process. In this study, it is used as a green binder to bind the urea together and form a fertilizer. The objective of the current research is to investigate the effect of biochar impregnation with urea on the N-nutrients retention in soils. The biochars were produced at heating temperatures of 300 °C and 700 °C for 3 hours with continuous nitrogen gas purging at 30 ml/min and a constant heating rate of 5 °C/min. The obtained biochars were characterized by XRD, Boehm titration, pH alkalinity, BET specific surface area and SEM. Boehm titration demonstrated a reduction of acidic functional groups with the increase of heating temperature, recorded as 1.3 and 0.3 mmol/g respectively for 300 °C and 700 °C. Conversely, biochar produced at higher temperature was reported to have a larger specific surface area of 5.4 m2/g. The impregnation was carried out on both biochars produced with molten urea. Results from mineralization showed that the sample with impregnation retained more nutrients in the soil compared to the un-impregnated sample, manifesting biochar as a potential material to be impregnated with urea for slow release and better nutrients retention in soil.